Neonatal Therapeutic Intervention Scoring System (NTISS) in Rural Country: Mortality and Length of Stay (LOS) Predictive Score in Preterm Infant - Desy Nurrosalia Wisnuwardani1 , Mahendra Tri Arif Sampurna2 , Martono Tri Utomo2 , Risa Etika2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Preterm infants need comprehensive management due to high risk of mortality and morbidity. Proper treatment in NICU can decrease the mortality risk in them, but some of them may take long time before they can go home. Neonatal Therapeutic Intervention Scoring System (NTISS) hopefully can be a predictive score for the mortality and Length of stay (LOS) of a preterm infant, yet, it’s use is still very limited in Indonesia. The authors aim to analyze NTISS to predict mortality and length of stay of preterm infants in Indonesia. Method: This retrospective study conducted in March 2017 and collected medical record data of preterm infants treated in NICU from July 2016 - March 2017. The inclusion criteria were infants with gestational age <37 weeks, treated at NICU> 24 hours and complete medical record data. NTISS total scores are collected after 24 hours at the NICU. Results: A total of 108 infants met the inclusion criteria. The ratio of NTISS scores had an area under the curve (area under curve / AUC) of 0.879 (95% CI 0.259-0.913) with cutoff at 20.2. it had 91.3% and 74.1% in sensitivity and specificity respectively; 48.8% and 96.9% in positive and negative predictive value respectively; positive likelihood ratio 3.52; negative likelihood ratio 0.12; and 77% inaccuracy. There was no correlation between NTISS scores and length of stay (p = 0.084). Conclusion: NTISS can be used to predict the mortality of preterm infants.